One-Child Policy, Marriage Distortion, and Welfare Loss - Wei Huang; Yi Zhou (Institute for the Study of Labor (IZA), 2015)
Using plausibly exogenous variations in the ethnicity-specific assigned birth quotas and different fertility penalties across Chinese provinces over time, we provide new evidence for the transferable utility model by showing how China's One-Child Policy induced a significantly higher unmarried rate among the population and more interethnic marriages in China. We further develop the model and find that a policy-induced welfare loss originates from not only restricted fertility but also from marriage distortion, and both depend solely on the corresponding reduced-form elasticities. Our calculations suggest that the total welfare loss is around 4.9 percent of yearly household income, with marriage distortion contributing 17 percent of this welfare loss. These findings highlight the importance of taking into consideration the unintended behavioral responses to public policies and the corresponding social consequences.
Keywords: H20; I31; J12; J13; J18; 330; One-Child Policy; marriage distortion; welfare loss